Analisis Kegiatan Ekstrakulikuler Kepramukaan untuk Membangun Karakter Disiplin Siswa di MI Al Hidayah 1 Kecamatan Cilodong Kota Depok - Saidatul Aliyah; Herlina; Siti Hadiyanti Dini I (Mimbar Kampus: Jurnal Pendidikan dan Agama Islam, 2024)
Scout activities are carried out in an organized manner by students outside of study hours. Scout activities have groups based on the age of the students. Scout activities have the aim of forming students' disciplined character. This research was conducted at Madrasah Ibtidaiyah Al – Hidayah I Cilodong Depok. The results of observations on extracurricular activities show that there are still students who are not good at discipline, it is proven that many of them are excused from scouting for family events and other reasons. This research aims to analyze "Analysis of Scouting Extracurricular Activities in Building Students' Disciplined Character at MI Al Hidayah 1 Cilodong Depok". This research is qualitative research. The data used in this research is qualitative data. Qualitative data is a type of data that is not in the form of numbers, but descriptive, narrative. The formation of students' disciplinary character can be formed due to the elements of disciplinary character, namely rules, punishment, rewards and consistency. The coach's strategy for forming students' disciplined character is to provide role models, examples and habituation to discipline. The obstacles experienced by students are external factors and internal factors which hinder discipline. The solution is for the coach to meet with the parents, then look for a solution together. Next, move the activity schedule to non-Saturdays, so that students create enthusiasm for learning, rest earlier for students who learn quickly, for those who have difficulty memorizing, look for more effective learning styles.